EXPLORING MATTHEW'S FEAR AS A MOVE TO INDIVIDUATION IN LISA THOMPSON'S “THE GOLDFISH BOY” - Danu Wahyono; Muhammad Loverio (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2026)
This research aims to analyse Matthew's fear as a move toward individuation in Lisa Thompson's novel The Goldfish Boy by examining how fear shapes his behavior and contributes to Matthew's journey toward individuation. His fear is related to his guilt over his baby brother's death, and an extreme fear of germs and social interaction forms the main psychological conflicts that curtail his everyday life. A psychological approach based on Carl Jung’s theory of individuation is used in this study to investigate how Matthew’s fears reveal deeper unconscious elements, including his persona, anima/animus, and the shadow that is a suppressed guilt and unresolved trauma, and how these elements relate to the individuation process, especially the stages that guide Matthew toward discovering his true self. This qualitative-descriptive research identifies dialogues, narrative descriptions, and events that reflect the psychological struggle of Matthew through close reading of the novel. The findings demonstrate that fear serves both as an obstacle and as a catalyst in Matthew’s development. His guilt-driven fear leads him to isolation, compulsive cleaning, and avoidance of social interaction, showing how fear can consume an individual and result in emotional suffering. However, Teddy Dawson’s disappearance becomes a turning point that forces Matthew to confront his fears, break his avoidance patterns, and gradually integrate the repressed parts of himself. When faced rather than avoided, Matthew’s fears transform into a driving force that enables personal growth, deeper self-understanding, and the early stages of individuation, helping him move toward self-awareness, emotional balance, and a more integrated sense of identity.